NUPENGASSAN and the struggle against precarious work in the Nigerian oil and gas industry - Baba Aye (International Labour Organization (ILO), 2017)
The literature on informality is largely focused on the 'informal sector' as a marginal or peripheral sphere of national economic life, beyond the pale of the leading formal industrial sectors, particularly in developing countries. This paper interrogates informalisation of labour and employment relations within the formal sector as its point of departure. The contemporary prevalence of precarious work which this foster is identified as a key element of the neoliberal agenda for keeping wages low and for maintaining social control. A mix of strategies rooted in unions' organising power and which attains some level of institutionalisation of social dialogue, such as the expansion of collective bargaining structures and mechanisms to represent 'casual workers' is seen as fundamental for a transition to the formalisation of their status, and the curtailing of employers' unilateralist power in the world of work. The experiences of oil and gas workers' unions (collectively known as NUPENGASSAN) in Nigeria is utilised to illustrate this argument. The paper situates NUPENGASSAN's organising and representation of contract staffers within the context of how labour and employment relations are informalised from above in the sector. The creative multi-faceted organising strategies the unions utilised for building workers' power and pushing through social dialogue in upstream, midstream and downstream work situations are examined. The Guidelines on Labour Administration issued by the Federal Government in 2011 is a milestone marking the success of this approach. The paper however also notes the at times surreptitious and at times more brazen means of perpetuating precarity and undermining bi-partite social dialogue utilised by employers, including the use of landmines in labour law. NUPENGASSAN's consolidation of creative organising of union structure, mass mobilisation of members, and aggressive advocacy could help shape public opinion against such hollowing out of the spirit of the Guidelines by government and private sector employers. The unions will also benefit from greater collaboration with the radical civil society movement, and civic organisations in the communities their members work in. Despite the daunting challenges that still lie ahead, other unions can learn from the NUPENGASSAN struggle, as they combat the anti-worker regimen of labour flexibilization.
Keywords: 330